Diversidade genética e fenotípica em ‘Flying Dragon’ (Poncirus trifoliata var. monstrosa (T. Ito)) micropropagado - Baptista, Leticia Zonta (Universidade Federal de São Carlos, 2023)
Brazilian citriculture is of great importance in world agribusiness since 41% world’s orange production comes from national orchards. With the entry of HLB into orchards, new strategies are needed to avoid loss of productivity, such as high density. Due to the high demand of plants and low supply of seeds, micropropagation of citrus rootstocks is an alternative in the production of seedlings, as it allows clonal mass production in a reduced space, not depending on seeds and eliminating the need to discard germinated zygotic embryos. However, after undergoing continuous stress exerted by tissue culture and high concentrations of growth regulators, the material may show (epi)genetic and/or phenotypic changes, called somaclonal variation. These changes can be characterized as morphological, physiological, and molecular, showing changes in the ploidy level that can be identified by molecular markers and flow cytometry. The objective of this work was to study the possible morphological and phenotypic plant variation of 100 'Flying Dragon' plants submitted to the micropropagation process for more than two years and 25 subcultures in WPM culture medium and 100 plants originating from seed. For the morphological characterization, evaluations of color, leaf margin, presence of thorn, measurement of height and diameter of stem and leaf area were performed. For the genetic characterization SSR molecular markers and flow cytometry were used. 30 pairs of microsatellite primers, previously developed, were used in 100 micropropagated plants, 5 plants produced by seeds and compared to 3 FMVI plants. For cytometry, were used 100 micropropagated plants, 100 plants produced by seeds and compared to the 3 plants that provided initial plant material according to the availability of leaf material. The morphological results were uniform between samples and between origins compared to the source plant. Twenty-seven SSR markers amplified fragments, 19 (70%) allowed the visualization of only one allele (DNA fragment) and 8 amplified two alleles. The size of the amplified fragments ranged from 100 to 200 bp. Flow cytometry analysis of 100 micropropagated plants and 100 seed plants showed mean values of nuclear volume of 171.43±8.99 for seed plants and 189.47±7.03 for micropropagated ones. The conclusion with these results is that the process of micropropagation by somatic organogenesis in 'Flying Dragon' plants after 25 subcultures in WPM culture medium is stable.
Genetic and phenotypic diversity in micropropagated ‘Flying Dragon’ (Poncirus trifoliata var. monstrosa (T. Ito))
Keywords: Micropropagação; SSR; Citometria; Flying Dragon; Micropropagation; Cytometry; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA